INVESTIGATION OF TADF PROPERTIES OF NOVEL DONOR-ACCEPTOR TYPE PYRAZINE DERIVATIVES - Zeynep Turhan Irak; Ayşegül Gümüş; Selçuk Gümüş (Journal of the Chilean Chemical Society, 2019)
In this study 2,3-dicyanopyrazine based acceptor was combined with donors to obtain Donor-Acceptor type potential thermally activated delayed fluorescence (TADF) emitters (1-10). All molecules’ structural and electronic properties were computed theoretically at the level of Density Functional Theory (DFT) and Time Dependent Density Functional Theory (TDDFT) with the application of three different hybrid functionals. Most of the designed structures have been found to possess the potential to be TADF compounds because they have very narrow energy gap between their first excited singlet and triplet states. As a result, 6-10 molecular pyrazine derivative has been calculated as the best candidate for the purpose. Moreover, having 0.90 eV interfrontier molecular orbital energy band gap, compound 6 has a very strong potential to serve as an efficient OLED material.